IDENTIFIKASI PROVENANCE SELAMA MIOSEN TENGAH HINGGA PLIOSEN DICEKUNGAN SERAYU UTARA BAGIAN BARAT DI DAERAH KUNINGAN JAWA BARAT - Bernadeta Subandini Astuti (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2016)
Basinareaof western North Serayuis potentially for hydrocarbon such assource rock, reservoir, cap rock and manife stations of the oil. The basin composed by turbit current sediments during the Middle Mioceneto Pliocene. Petrographic analysis of the mineral quartz, feldspar and lithikh as been done to identify the provenance of rocks potentially hydrocarbon. Turbid currents bringrich sedimentlithic, that indicate origin of themagmatic arc. Lithicis reduced to wards younger and east ward. Reduced lithikindication of declining volcanism. Indications reduced lithikisdeclining volcanism. Rocks of western North Serayu basin, that is origin of this magmaticarcin several places found dead oil and oil see page, especially on the rock that show scoarsening up ward or decreasing the current sea level.